Modelling the impact of sodium intake on cardiovascular disease mortality in Mexico - Jorge Vargas-Meza; Eduardo Augusto Fernandes Nilson; Claudia Nieto; Neha Khandpur; Edgar Denova-Gutiérrez; Isabel Valero-Morales; Simón Barquera; Ismael Campos-Nonato (BMC, 2023)
Abstract Background Cardiovascular diseases (CVD) represent the main cause of death in Mexico, while high blood pressure is suffered by about half of the adult population. Sodium intake is one of the main risk factors for these diseases. The Mexican adult population consumes about 3.1 g/day, an amount that exceeds what is recommended by the World Health Organization (WHO) < 2 g sodium/day. The objective of this study was to estimate the impact of reducing sodium intake on CVD mortality in Mexico using a scenario simulation model. Methods The Integrated Model of Preventable Risk (PRIME) was used to estimate the number of deaths prevented or postponed (DPP) due to CVD in the Mexican adult population following the following sodium intake reduction scenarios: (a) according to the WHO recommendations; (b) an "optimistic" reduction of 30%; and (c) an "intermediate" reduction of 10%. Results The results show that a total of 27,700 CVD deaths could be prevented or postponed for scenario A, 13,900 deaths for scenario B, and 5,800 for scenario C. For all scenarios, the highest percentages of DPP by type of CVD are related to ischemic heart disease, hypertensive disease, and stroke. Conclusions The results show that if Mexico considers implementing policies with greater impact to reduce sodium/salt consumption, a significant number of deaths from CVD could be prevented or postponed.